Shortening the Potential Duration of Unemployment Benefits and Labor Market Outcomes: Evidence from a Natural Experiment in Germany - Inna Petrunyk; Christian Pfeifer (Institute of Labor Economics (IZA), 2018)
This paper explores the effects of a major reform of unemployment benefits in Germany on the labor market outcomes of individuals with some health impairment. The reform induced a substantial reduction in the potential duration of regular unemployment benefits for older workers. This work analyzes the reform in a wider framework of institutional interactions, which allows us to distinguish between its intended and unintended effects. Our results provide causal evidence for a significant decrease in the number of days in unemployment benefits and increase in the number of days in employment. However, they also suggest a significant increase in the number of days in unemployment assistance, granted upon exhaustion of unemployment benefits. Transitions to unemployment assistance represent an unintended effect, limiting the success of a policy change that aims to increase labor supply via reductions in the generosity of the unemployment insurance system.
Keywords: I1; J2; J65; 330; policy evaluation; labor market reform; unemployment insurance; difference-in-differences